Designed for safety: characteristics and trends in crime prevention through environmental design research - Yu Wen; Hong Qi; Tao Long; Xinjia Zhang (Journal of Asian Architecture and Building Engineering)
Under the dual pressures of repeated impacts from the pandemic and global economic downturn, the deterioration trend of social security is evident. In 2021 and 2022, the United Nations consecutively emphasized the centrality of reducing and preventing recidivism, aiming to foster research and practices in crime prevention. Developing and applying crime prevention through environmental design (CPTED) theory provides a viable approach to reducing crime. Utilizing the relevant literature on environmental design for crime prevention from the Web of Science Core Collection database and employing Cite Space software, this study systematically delineates the research trajectory of crime prevention through environmental design. The research uses bibliometrics and literature analysis methods to identify research hotspots and trends in the field. Building upon these findings, the study proposes that future research in CPTED should systematically explore the spatiotemporal heterogeneity of the impact of urban built and social environments on crime. It also advocates for in-depth investigations into the long-term causal relationship between environmental features and crime under the framework of CPTED. The study emphasizes the exploration of the local applicability of CPTED theory under conditions of multiculturalism and regional differences. This helps to propose crime prevention strategies for new social issues and crime patterns, thereby providing strong support for the sustainable development of cities.